2017
DOI: 10.5195/jyd.2017.474
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Curiosity, Inquiry, and Scientific Thinking in Elementary School Students: Impact of the NE STEM 4U Intervention

Abstract: In this qualitative study, we assessed the impact of the NE STEM 4U intervention on elementary school youth in terms of excitement, curiosity, and STEM concepts. The NE STEM 4U intervention incorporates a problem-based learning theoretical framework in an after-school time, weekly or twice-weekly intervention. We assessed student performance over two academic years of participation in the intervention using the Dimensions of Success observational tool. Ultimately, we link this mentor-led program with increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Although research suggests that some teaching methods provide more positive results than others (Akkus et al, 2007;Maxwell et al, 2015), it is clear that early positive engagement in STEM is critical to young students' future interest and participation in STEM (Bybee & Fuchs, 2006;Dejarnette, 2016). In addition to in-school experiences, early experiences outside of school are also critical for early engagement and interest in STEM (Leas et al, 2017). Students may be exposed to early STEM activities through different types of informal STEM programs (Bevan & Michalchik, 2013) and/or activities within a home environment such as cooking (Finn & Vandermaas-Peeler, 2013), gardening (Ruby et al, 2007), and watching television (Dou et al, 2019;Jarman & McClune, 2007).…”
Section: Early Stem Experiences and Stem Identitymentioning
confidence: 99%
“…Although research suggests that some teaching methods provide more positive results than others (Akkus et al, 2007;Maxwell et al, 2015), it is clear that early positive engagement in STEM is critical to young students' future interest and participation in STEM (Bybee & Fuchs, 2006;Dejarnette, 2016). In addition to in-school experiences, early experiences outside of school are also critical for early engagement and interest in STEM (Leas et al, 2017). Students may be exposed to early STEM activities through different types of informal STEM programs (Bevan & Michalchik, 2013) and/or activities within a home environment such as cooking (Finn & Vandermaas-Peeler, 2013), gardening (Ruby et al, 2007), and watching television (Dou et al, 2019;Jarman & McClune, 2007).…”
Section: Early Stem Experiences and Stem Identitymentioning
confidence: 99%
“…Detailed demographic information regarding the parti­cipants in the current study is available in Supplemental Table 1. Additionally, the demographics of the youth (i.e., K–8 participants) are included in Cutucache et al (2016) and Leas et al (2017), but are summarized here: >50% of participants are African American, Latino, or declare both African American and Latino as their race, and just under 50% are Caucasian, Asian, or Pacific Islander students. All schools served in the Omaha Public School District have free or reduced lunch rates >47%, with the majority of the schools served being at 97% free and reduced lunch rates or higher (Leas et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Since the program started, the initiating institution has experienced tremendous growth and productivity in research that led to a research-intensive (i.e., R2) designation. Previous studies documenting the impact of the NE STEM 4U program on youth outcomes showed evidence of gains in preferences for STEM careers among youth in 4th through 8th grade, as well as better preparation and persistence in STEM paths among college students (Leas et al, 2017).…”
Section: The Institution At the Site Of Originmentioning
confidence: 98%
“…In an effort to address challenges to persistence in STEM fields in college, such as early life STEM preferences (e.g., 4th to 8th grade) and post-secondary (i.e., undergraduate) student preparation and retention, we created the program NE STEM 4U (NE indicates Nebraska, a state in the central United States, where the program originated; Cutucache et al, 2016;Leas et al, 2017). The NE STEM 4U program began at a large, metropolitan university in an urban setting that (at the time) offered a limited number of masters and doctoral programs.…”
Section: The Institution At the Site Of Originmentioning
confidence: 99%
See 1 more Smart Citation